2018
DOI: 10.1590/1807-1929/agriambi.v22n5p360-365
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and sanitary quality of maize seeds preconditioned in ozonated water

Abstract: A B S T R A C TThe technique of controlled hydration of seeds has been used as a method of physiological conditioning to improve their performance in the field. Solution aeration with ozone gas is a promising option in controlling phytopathogens. The objective of the present study was to evaluate the physiological and sanitary quality of maize seeds preconditioned in ozonated water. In the evaluation of the physiological and sanitary quality, maize seeds were submitted to four concentrations of ozone gas (0, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
8
0
3
Order By: Relevance
“…O aumento da velocidade de emergência pode ser atribuído à ativação do mecanismo de reparação celular, em que leva a reorganização dos componentes estruturais de célula (MAXIMIANO et al, 2018).…”
Section: Resultsunclassified
“…O aumento da velocidade de emergência pode ser atribuído à ativação do mecanismo de reparação celular, em que leva a reorganização dos componentes estruturais de célula (MAXIMIANO et al, 2018).…”
Section: Resultsunclassified
“…Segundo Maximiano et al (2018) quando realizado ou não pré-embebição de sementes de milho com água ozonizada em diferentes combinações de tempo e concentrações, a incidência de Fusarium spp. chegou a ser igual a 100%, podendo ter sido favorecido pela água disponível na camada superficial das sementes.…”
Section: Discussionunclassified
“…It is important to highlight that in the present study, the gas inlet concentration was lower than that used by Violleau et al (2008), which certainly influenced the obtained results. Maximiano et al (2018) found that ozone in aqueous media intensified the initial development of corn seedlings. Sudhakar et al (2011) stated that ozone accelerated the germination and development of tomato seedlings, causing a However, it is noteworthy that there are reports in the literature that indicate a positive effect of ozonation on corn seeds (Violleau et al, 2008;Maximiano, Carmona, Souza, Alencar, & Blum, 2018) and tomatoes (Sudhakar et al, 2011).…”
Section: Physiological Quality Of Ozonated Quinoa Seedsmentioning
confidence: 99%
“…Regarding the mean values of NSL (Figure 3A), SL (Figure 3B), and RL (Figure 3C), the variation remained between 7.8 and 10.5 cm, 3.4 and 4.7 cm, and 4.4 and 5.9 cm, respectively. However, it is noteworthy that there are reports in the literature that indicate a positive effect of ozonation on corn seeds (Violleau et al, 2008;Maximiano, Carmona, Souza, Alencar, & Blum, 2018) and tomatoes (Sudhakar et al, 2011). Violleau et al (2008) observed a positive effect of ozone gas on germination and root length when they analyzed ozonized corn seeds, at an ozone concentration of 20 mg L -1 (≈9.340 ppm) for periods of 6.8 and 20.5 min.…”
Section: Physiological Quality Of Ozonated Quinoa Seedsmentioning
confidence: 99%